KINERJA PEGAWAI LEMBAGA PEMASYARAKATAN ANAK: PERAN PSYCHOLOGICAL CAPITAL DAN WORKPLACE WELL-BEING - Esterina, Meriam; Patria Jati Kusuma; Ridla Salima Hanum (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
Employee performance is important to be considered because it supports the achievement of organizational goals. The special juvenile correctional institution as an institution under the Ministry of Law and Human Rights is tasked with providing guidance to foster children. The weight of responsibility can affect employee performance. This study was conducted at the Class I Kutoarjo Special Juvenile Correctional Institution. The population of this study were ASN employees of the Class I Kutoarjo Special Juvenile Correctional Institution. The sampling technique used was saturated sampling, with a sample size of 42 people. The purpose of this study was to determine the effect of psychological capital and workplace well-being on performance. This study is a quantitative study using multiple regression analysis. The research instruments were in the form of a psychological capital questionnaire, a workplace well-being questionnaire, and a performance questionnaire. The data obtained were then analyzed using SPSS. The results showed that there was a significant positive effect simultaneously and partially of psychological capital and workplace well-being on performance, with an R square value of 85.1%.